Mini Kompetisi Woodball Sebagai Kegiatan Pengenalan dan Pengembangan Aktivitas Fisik (Olahraga) Bagi Masyarakat Di Pamulang Permai Kota Tangerang Selatan - Ika Yulianingsih (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2023)
Woodball is a new sport that has developed since 2006. The game, which resembles golf, is very suitable for all people from childhood to old age. Quite easy to play and can be played at home. Besides being healthy, Woodball has the characteristics of a fun sport, recreation and of course activities. There is a need for an introduction to the wider community to realize the vision and mission of building sports in society. Socializing sports and cultivating the community through Woodball sports. The purpose of this community service activity is to introduce and develop physical activity through Woodball sports to the community, especially in the Pamulang Permai 1 area, West Pamulang Village, Pamulang District, South Tangerang City. The method of this activity is carried out by socializing and implementing the practice of playing by competing. Based on the results of the activity, quite a lot of participants took part in the mini competition, from junior to senior categories. It is hoped that through many competitive activities such as mini competitions, many people will be interested in developing physical activity through sports for all ages.